LENDING RELATIONSHIP DAN DAMPAKNYA TERHADAP AKSES KREDIT BAGI USAHA KECIL DAN MIKRO: (STUDI PADA USAHA SIMPAN PINJAM OLEH BADAN USAHA MILIK DESA/BUMDES DI PULAU LOMBOK) - Embun Suryani; Donny Oktaviansyah; Adi Septiawan (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2020)
The informal sector in developing countries like Indonesia is able to grow rapidly and is able to absorb labor. However, the ability to access credit is one of the main obstacles for the development and growth of Small and Micro Enterprises (SMEs). Microcredit is characterized with the existence of information asymmetry, for that we need a different approach in distributing financing for SMEs, one of which is to apply the approach lending relationship. The research was conducted at 12 Lembaga Keuangan Mikro (LKM) BUMDes in Lombok. The results indicate that the variable lending relationship positively affects credit approval and the period for credit approval submitted by customers. It means that loan approval and approval timeframes increase with the increase in the intensity of the relationship between LKM BUMDes and micro customers. The interest rate and the application of collateral do not have a positive effect on lending relationships. The implication of these results is to illustrate the intensity of interactions between borrowers and lenders can provide credit access for micro customers. Another implication shows that the microcredit distribution strategy must be carried out by building continuous relationships with customers to reduce the occurrence of information asymmetry in micro-credit distributionKeywords :Asymmetric information, intensity of relationship, interest rate, collateral, micro credit, LKM BUMDes